An Analysis of Word Formation Processes in William Shakespeare's poetries - M. Yusril Rizqi Hidayat; Alfiyana Ni’mah Fadhila (PRASASTI: Journal of Linguistics, 2024)
This study aims to analyze the types of word formation processes in three poems of William Shakespeare entitled "All the world's stage", "Fear no more", and "Shall I compare thee to a summer's day?". The researcher found six types of word formation, such as derivation, blending, borrowing, fusion, clipping, and multiple processes. Because many words are rarely heard, it inspired the author to examine the word formation process in the poem.  This research is a qualitative descriptive. The researcher used the method of analyzing the data and reading the poem many times to get detailed and concrete data. a lot of new things were obtained in this research. The findings of this research are as follows: 64% of suffixes, 4% of combining prefix-suffix, 1% of blending, 1% of borrowing, 19% of compounding, 1% of clipping, 10% of multiple process.